2021
DOI: 10.1111/1467-8500.12497
|View full text |Cite
|
Sign up to set email alerts
|

Organisations adapting to dual aspirations of individualisation and collaboration in the National Disability Insurance Scheme (NDIS) market

Abstract: Disability support is often provided at the interface with other human services such as health, education, and employment agencies. This can present many organisational problems for people receiving support and the organisations that provide it. Individualised funding is one attempt to ease problems of fragmentation and unmet needs, but perversely, it introduces further interface complexities as organisations consider how to manage their service provision and financial structures.Drawing on interviews with 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 42 publications
(50 reference statements)
0
31
0
Order By: Relevance
“…However, this limited research reveals that formal support systems are inadequate [ 5 , 16 , 18 , 22 , 54 ] despite the multiple service providers involved in the lives of people with SPMI [ 14 , 17 , 51 ]. Furthermore, even though mental health, NDIS, and palliative care providers share person-centred values [ 15 , 19 , 40 , 92 , 93 ], collaboration between providers, though highly recommended and encouraged, is poor, limited or non-existent [ 15 , 16 , 18 , 21 , 22 , 27 , 38 , 40 , 53 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. The NDIS does not fund case management or care coordination, a recognised and highly valued role in mental health systems [ 100 , 101 ], to the detriment of NDIS participants with complex support needs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this limited research reveals that formal support systems are inadequate [ 5 , 16 , 18 , 22 , 54 ] despite the multiple service providers involved in the lives of people with SPMI [ 14 , 17 , 51 ]. Furthermore, even though mental health, NDIS, and palliative care providers share person-centred values [ 15 , 19 , 40 , 92 , 93 ], collaboration between providers, though highly recommended and encouraged, is poor, limited or non-existent [ 15 , 16 , 18 , 21 , 22 , 27 , 38 , 40 , 53 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. The NDIS does not fund case management or care coordination, a recognised and highly valued role in mental health systems [ 100 , 101 ], to the detriment of NDIS participants with complex support needs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to trends in human services in some European countries, the Australian Government designed the NDIS to deliver individualised or self-directed support to people with disabilities [ 95 , 113 ]. These funding models help empower NDIS participants [ 114 ] and ratify Australia’s obligations under the UNCRPD [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that transitioning to a market‐based scheme, although improving service access and quality for some people with disability, might disadvantage others (Backhouse, 2017; Carey et al, 2018; Muir & Salignac, 2017). Market forces can have unintended consequences, with potential risks of, for example, market gaps for certain services (Carey et al, 2018), “cream‐skimming” of high value customers (Backhouse, 2017), disincentives for inter‐provider collaboration (Foster et al, 2021; Green et al, 2018) or exploitation of vulnerable participants (Russi, 2014). Although various mechanisms exist to regulate and “steward” the market (Carey et al, 2018), it is conceivable that unintended market dynamics could have emerged and affected numbers in RAC.…”
Section: Introductionmentioning
confidence: 99%